Impact of anastomotic complications on outcome after laparoscopic gastrectomy for early gastric cancer - Nagasako, Y.; Satoh, S.; Isogaki, J.; Inaba, K.; Taniguchi, K.; Uyama, I. (British journal of surgery, 2012)
Background: The effects of anastomotic complications after laparoscopically assisted gastrectomy (LAG) have not been studied widely. The aims of this observational study were to identify potential factors that predict anastomotic complications and investigate the impact of anastomotic complications in patients undergoing gastrectomy for early gastric cancer. Methods: The study included consecutive patients with histologically proven T1 gastric adenocarcinoma treated by LAG with regional lymphadenectomy between August 1997 and March 2008, who had not received neoadjuvant chemotherapy. Anastomotic complications included anastomotic leakage, stricture and remnant gastric stasis of grade II or higher (modified Clavien classification) and were identified by clinical assessment and confirmatory investigation. Predictive factors for the development of anastomotic complications were identified by univariable and multivariable analyses. Long‐term survival with or without anastomotic complications was examined. Results: Anastomotic complications occurred in 37 (9·3 per cent) of 400 patients. Multivariable analysis indicated surgeon experience as the only independent predictor of anastomotic complications (hazard ratio 4·40, 95 per cent confidence interval 2·04 to 9·53; P < 0·001). Patients with anastomotic complications had a significantly worse overall 5‐year survival rate than those without (81 versus 94·2 per cent; P = 0·009). Conclusion: Anastomotic complications after LAG lead to worse long‐term survival. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Reduced long‐term survival